Giant cervical myoma associated with actinomycosis: a rare cause of uremia - Sahin, Banuhan; Karabulut, Aysun; Demirtas, Omer; Ertur, Habibe Radiye; Karabulut, Nevzat (The European Research Journal, 2016)
Myomas are commonly seen benign tumors of the uterus; they may cause a great variety of symptoms depending on the location. Herein, we presented an unusual case of giant cervical myoma with associated actinomycosis resulting in bilateral hydronephrosis and uremia. A 42-year-old woman was admitted to emergency service with anuria and confusion. She had an intra-abdominal mass extending 4-5 cm above the level of umbilicus. The hemoglobin level was 5.1 g/dl and creatinine level was 5.2 mg/dl. Magnetic resonance imaging revealed enlarged uterus with intrauterine device which was displaced up above the level of umbilicus due to a large cervical mass measuring 16.5x11.5x12 cm, tortuous hydroureters on both sites and left tuba ovarian abscess. A huge cervical lobulated mass which was pressing both ureters and filling the lower abdomen, and left tuba ovarian abscess with dense adhesions which was created by actinomycotic infection were detected on explorative laparotomy. Uremia was normalized gradually following hysterectomy, and the patient was discharged with penicillin treatment. Although myomas are the benign tumors, they may mimic the genital malignancy, and may cause life-threatening complications such as renal failure and uremia.